Seasonal changes in haematological and biochemical profile of dairy cows in high altitude cold desert - GIRI, ARUP; BHARTI, VIJAY K; KALIA, S; RAVINDRAN, V; RANJAN, P; KUNDAN, T RAJ; KUMAR, B (The Indian Journal of Animal Sciences, 2017)
The present study was undertaken to evaluate haematological and biochemical parameters with response to milk production of Jersey cows at high altitude in 2 different seasons (summer and winter). For each period, ambient temperature and relative humidity were recorded and the temperature-humidity index (THI) was calculated as indicator of thermal comfort zone for cattle. Clinically healthy lactating Jersey crossbred cows (70:70 in each season) were selected for this study. A significant increase in RBC, Hb, and HCT was recorded in winter as compared to summer. Furthermore, MCV, MCH, MCHC and PLT levels also exhibited the similar trend; whereas, the WBC, lymphocyte, monocytes, and granulocytes values were higher in summer compared to winter. Glucose and aspartate aminotransferase (AST) level showed a significant increase in summer but level of albumin went significantly higher in winter. Milk production level was significantly higher in summer. These results provided an insight into the haematological and biochemical responses of Jersey crossbred cows to different environmental conditions. Hence, this study will be helpful for the better dairy cattle management in different seasons for higher production at the cold arid high altitude region.